Enhancing Perceived Employability through Digital, Analytical, and AI Oriented Skills in Accounting - Perdana Putri, Adhevia; Dwianto, Agus (Inovasi Analisis Data, 2025)
Objective: Analyze the influence of accounting technical skills, digital technology skills, data analytics skills, and soft skills on perceived employability among accounting students in Indonesia, with artificial intelligence (AI) orientation readiness as a moderating variable.Methods: The present study employed a quantitative methodology, surveying 700 accounting students from state and private universities in Surakarta. A structured questionnaire was utilized to collect data, which was then analyzed HTMT to (PLS-SEM) to validate the proposed relationships and moderation effects.Results: The findings of the study indicated a significant relationship between all four skill categories i.e., accounting, technical skills, digital technology skills, data analytic skills, and soft skills and students' perceptions of employability. Secondly, the AI Orientation Readiness variable significantly moderates these relationships, particularly amplifying the impact of digital and analytical competencies.Novelty: This paper is an original contribution to the field of accounting education, with a focus on the incorporation of artificial intelligence (AI) readiness into the employability framework. This topic is particularly under-researched, especially in the context of developing economies. Furthermore, it addresses a significant research gap by establishing a link between future competencies and AI preparedness within the context of the lean 5th Industry.Research Implications: The findings of the study indicate that there is an urgent requirement for reform of accounting curricula, for the introduction of AI-related content, and for the development of cross-disciplinary skills. The report also provides policy recommendations, curriculum guidelines, and sample assignments to assist secondary schools and institutions of higher education in educating and supporting graduates in technology-led economies.